Undrained bearing capacity of obliquely-eccentrically loaded shallow foundations overlying a heterogeneous and inherently anisotropic clay deposit - Maedeh Nasiri Pishvari; Hessam Fathipour; Suraparb Keawsawasvong; Boonchai Ukritchon; Meghdad Payan; Reza Jamshidi Chenari (Journal of Rock Mechanics and Geotechnical Engineering)
Clay deposits typically exhibit significant degrees of heterogeneity and anisotropy in their strength and stiffness properties. Such non-monotonic responses can significantly impact the stability analysis and design of overlying shallow foundations. In this study, the undrained bearing capacity of shallow foundations resting on inhomogeneous and anisotropic clay layers subjected to oblique-eccentric combined loading is investigated through a comprehensive series of finite element limit analysis (FELA) based on the well-established lower-bound theorem and second-order cone programming (SOCP). The heterogeneity of normally consolidated (NC) clays is simulated by adopting a well-known general model of undrained shear strength increasing linearly with depth. In contrast, for overconsolidated (OC) clays, the variation of undrained shear strength with depth is considered to follow a bilinear trend. Furthermore, the inherent anisotropy is accounted for by adopting different values of undrained shear strength along different directions within the soil medium, employing an iterative-based algorithm. The results of numerical simulations are utilized to investigate the influences of natural soil heterogeneity and inherent anisotropy on the ultimate bearing capacity, failure envelope, and failure mechanism of shallow foundations subjected to the various combinations of vertical-horizontal (V-H) and vertical-moment (V-M) loads.